Strong coupling and high-contrast all-optical modulation in atomic cladding waveguides - Liron Stern (Nature Portfolio, 2017)
Studying the effects of quantum coherence and shifts in nanoscale atomic cladding waveguides is challenging. Here, Sternet al. construct a highly compact serpentine silicon-nitride atomic vapour cladding waveguide and observe phenomena such as van-der-Waals shifts, dynamical stark shifts and strong coupling.